Molecular and Serological Detection of Helicobacter Pylori Bacteria in Patients with Gastrointestinal Tract Infections - Mohammed, Doaa; Hind Abdallah Salih (University of Thi-Qar Journal of Science, 2025)
Helicobacter pylori is closely associated with gastrointestinal diseases, which are among the most common health problems worldwide. This study aimed to detect H. pylori using serological and molecular diagnostic methods to enhance the accuracy and reliability of testing. Samples were collected from the Digestive System Center/Imam Hussein Teaching Hospital in Thi Qar between October 2024 and March 2025. These included 115 patients of both sexes and ages with gastrointestinal diseases. Serological and molecular tests were performed to detect H. pylori. 45 stool samples were collected; antigen testing was performed, and 20 samples (44.4%) were positive. These samples were then molecularly diagnosed by polymerase chain reaction (PCR), with the following results: H. pylori infection was diagnosed using PCR targeting 16sRNA in 3 out of 20 stool samples (15%). The diagnosis was also confirmed by detecting the virulence factors VacAs1/s2 and CagA, with VacAs1/s2 detected in 3(100%) and CagA in 2(66.66%) patients with gastrointestinal disease. Seventy blood samples were collected, and the H. pylori detection rate using antibody testing was 31(44.28%). The results of this study demonstrated that combining serological and molecular diagnostic methods improves the accuracy of H. pylori detection in patients.